The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.enbuild.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Short-term load forecasting in a non-residential building contrasting models and attributes

Abstract: An accurate short-term load forecasting system allows an optimum daily operation of the power system and a suitable process of decision-making, such as with regard to control measures, resource planning or initial investment, to be achieved. In a previous work, the authors demonstrated that an SVR model to forecast the electric load in a non-residential building using only the temperature and occupancy of the building as attributes is the one that gives the best balance of accuracy and computational cost for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(68 citation statements)
references
References 34 publications
0
53
0
1
Order By: Relevance
“…A majority of the literature focuses on a single building or a small set of buildings case studies. Other ML reviews in the building industry show similar libraries of work [11,12].…”
Section: Contemporary Building Energy Predictionmentioning
confidence: 80%
“…A majority of the literature focuses on a single building or a small set of buildings case studies. Other ML reviews in the building industry show similar libraries of work [11,12].…”
Section: Contemporary Building Energy Predictionmentioning
confidence: 80%
“…Wang and Srinivasan came to a similar conclusion in their review since they found that ensemble models have better prediction accuracy than single models (multiple linear regression [MLR], ANN, and SVR). Massana et al found similar results comparing ANN and linear regression for electric load forecasting of a nonresidential building, but in their application, SVR was slightly better than ANN. Zhao et al focused on the energy consumption prediction of office buildings using variable refrigerant volume (VRV) cooling systems.…”
Section: Neural Network Applications Over a Building's Lifementioning
confidence: 87%
“…As an integral part of the daily operational management of power utility, accuracy prediction of the short-term electric load in residential quarters is of great significance to urban power network planning and the electric power market operating. The overestimation will raise the operating cost while underestimation will lead to electricity shortage [3]. Because of the limited capacities on the user side, the load characteristics have less smoothing effect.…”
Section: Introductionmentioning
confidence: 99%